2018
DOI: 10.3390/coatings8040151
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Icing Performance of Hydrophobic Silicone–Acrylate Resin Coatings on Wind Blades

Abstract: Abstract:The icing of wind blades poses a serious threat to the operation of wind turbines. The application of superhydrophobic coatings on wind blades can serve as a potential anti-icing method. This study presents the findings of simulations of the icing environment of wind blades coated with hydrophobic silicone-acrylate resin in an artificial climate chamber. Artificial icing tests were performed on NACA7715 wind blades with four different silicone-acrylate resin coatings and on uncoated wind blades, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…With introduction of elastic deformation, the mismatch of E leads to localized stress at the tensile strain zone of elastomer and generates microfractures on the contact interface, accelerating the detachment of ice, which is denoted as Mode i in this work. The τ ice needs to be expressed by eq 1 in this moment: 4,8,33 EW t ice a (1) where W a represents the adhesion work of ice and t indicates the thickness of the soft coating. Notably, τ ice remains virtually unaffected by t at the micron scale and cannot to be infinitely reduced by increasing t. 11 The interpenetration of E51-EP and α,ω-PDMS can occur in any proportion via mutually independent curing reactions, 17 which endows the coating with a wider regulation range of E (0.6−1775.9 MPa) but still far from that of ice (3.3−3.6 GPa 34 ) (Figure 4a and Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…With introduction of elastic deformation, the mismatch of E leads to localized stress at the tensile strain zone of elastomer and generates microfractures on the contact interface, accelerating the detachment of ice, which is denoted as Mode i in this work. The τ ice needs to be expressed by eq 1 in this moment: 4,8,33 EW t ice a (1) where W a represents the adhesion work of ice and t indicates the thickness of the soft coating. Notably, τ ice remains virtually unaffected by t at the micron scale and cannot to be infinitely reduced by increasing t. 11 The interpenetration of E51-EP and α,ω-PDMS can occur in any proportion via mutually independent curing reactions, 17 which endows the coating with a wider regulation range of E (0.6−1775.9 MPa) but still far from that of ice (3.3−3.6 GPa 34 ) (Figure 4a and Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, even if icing event takes place, the retained air inflicts stress concentrations at the contact interface and impairs the ice bonds [58,84], resulting in up to 80%-90% lower energy necessary to maintain the protected surface free of ice [110,111]. Furthermore, the non-wetting Cassie-Baxter regime intrinsic for any superhydrophobic coating may support the freezing of droplets in a spherical shape (the so-called "ball-up" freezing), exemplified in Figure 4, and their facile dynamic detachment with low amount of applied thermal energy [105,[112][113][114].…”
Section: Modus Operandi Of Superhydrophobic Coatings For Passive Icinmentioning
confidence: 99%
“…They are, among others, characterized by (i) high energy efficiency and (ii) lower maintenance requirements/costs, (iii) without increasing the noise during operation. CNTs with their excellent thermal and electrical properties have been frequently considered as electrothermal heating elements. In the latest reports, Xu et al indicated that surfaces with higher hydrophobicity demonstrated better antiicing performance and benefited from active deicing: surfaces of increased hydrophobicity led to lower weight of cumulated ice and negligible ice adhesion. Nevertheless, full exploitation of typically entangled and defective CNTs is difficult because nonuniform and viscous dispersions are formed therefrom.…”
Section: Cnt Composites For Wtbs: Premises Manufacture Aspects and En...mentioning
confidence: 99%